PENGARUH ORGANIZATIONAL COMMITMENT, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION(STUDI KASUS PADA PT XYZ TANGERANG SELATAN) - Aliyah Vistani Riboch (2022)
This research is a quantitative study to determine the effect of organizational commitment, organizational citizenship behavior and job satisfaction on turnover intention. This study used samples from all permanent employees at the start-up company PT XYZ Tangerang Selatan. The number of samples in this study were 37 respondents from all permanent employees. The testing technique used in this study is path analysis using the Partial Least Square (PLS) method through SmartPLS 4.0 software. The results of this study obtained (1) organizational commitment has a partially significant effect on turnover intention, (2) organizational citizenship behavior has no partial significant effect on turnover intention, (3) job satisfaction has a partial significant effect on turnover intention, and (4) organizational commitment, organizational citizenship, and job satisfaction have a significant effect simultaneously or together on turnover intention.